A numerical solution for fluid flow in unsaturated porous medium (soil) - Timsina, Ramesh Chandra (The Nepali Mathematical Sciences Report, 2023)
We solve the two - dimensional mixed form Kirchhoff transformed Richards equation numerically using Crank - Nicolson scheme. This procedure has been integrated using cylindrical coordinates in an axially symmetric diffusion of flow in a homogeneous, isotropic porous medium.The soil has uniform hydraulic conductivity and no source or sink.The framework is cylindrical with a finite difference structured mesh.This procedure is particularly targeted at infiltration into dry soil, drainage, perched water table and flow through homogeneous materials. However, it is also applicable to any process involving flow through porous medium.The scheme we used is more accurate, comprehensive and is computationally efficient. It may provide a suitable basis for the implementation in large scale.